2015
DOI: 10.1186/s13024-015-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

Aβ-induced degradation of BMAL1 and CBP leads to circadian rhythm disruption in Alzheimer’s disease

Abstract: BackgroundPatients with Alzheimer’s disease (AD) frequently experience disruption of their circadian rhythms, but whether and how circadian clock molecules are perturbed by AD remains unknown. AD is an age-related neurological disorder and amyloid-β (Aβ) is one of major causative molecules in the pathogenesis of AD.ResultsIn this study, we investigated the role of Aβ in the regulation of clock molecules and circadian rhythm using an AD mouse model. These mice exhibited altered circadian behavior, and altered e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 55 publications
6
97
0
1
Order By: Relevance
“…Thus, dampening the rhythmicity of BMAL1 expression through circadian clock disruption likely plays a role in mediating astrogliosis, perhaps by restricting BMAL1 levels at certain key times of day. BMAL1 levels can be suppressed by several factors such as aging (Wyse and Coogan, 2010), inflammation (Curtis et al, 2015), or amyloid-beta (Song et al, 2015), all of which could potentially influence astrocyte activation and function in a BMAL1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, dampening the rhythmicity of BMAL1 expression through circadian clock disruption likely plays a role in mediating astrogliosis, perhaps by restricting BMAL1 levels at certain key times of day. BMAL1 levels can be suppressed by several factors such as aging (Wyse and Coogan, 2010), inflammation (Curtis et al, 2015), or amyloid-beta (Song et al, 2015), all of which could potentially influence astrocyte activation and function in a BMAL1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The core clock regulates transcription of thousands of genes in a highly tissue-specific manner, regulating cellular functions including metabolism, inflammation, and redox homeostasis (Bass and Takahashi, 2010). In addition to disrupted activity and sleep rhythms, dysregulated circadian gene expression patterns are also observed in neurodegenerative disease models and patients (Song et al, 2015; Breen et al, 2014; Cronin et al, 2017). However, the impact of clock dysfunction on neurological diseases of the brain remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to other disease specific changes in AD, BMAL1 protein levels may be directly affected by accumulation of amyloid-β (Aβ) during the course of AD pathology. A recent study reported that Aβ enhances the degradation of Bmal1 and Cbp, another circadian clock regulator, reducing binding of transcription factors to the Per2 promoter, and altering the oscillation of Per2 mRNA and protein expression in cell culture models and in the SCN of the 5×FAD transgenic mice model of AD [41]. …”
Section: Discussionmentioning
confidence: 99%
“…One post-mortem study demonstrated asynchronous clock gene expression between different brain regions in AD patients (50). Aβ can facilitate BMAL1 degradation in neuronal cells (51), suggesting that AD-related processes could directly influence cellular clock function. PD patients have blunted rhythms of clock gene expression in peripheral blood cells (52, 53), and transgenic mice overexpressing human alpha-synuclein, a neurodegenerative protein implicated in PD, develop behavioral and transcriptional circadian deficits (22).…”
Section: Circadian Function and Neurodegenerationmentioning
confidence: 99%